Energy System Transition – Spatial Policy and Electricity Grid Planning - Fromme, Jörg (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Energy politics tend to organize the balance between power production and power consumption at the international scale as good as possible, leaving the site selection for new power or storage plants to pan-European competition. As grid costs are paid for by consumers, such policy causes an increasing spatial concentration of power plants on most beneficial sites and a very extensive transmission grid expansion. In civil society in contrast, the intent of “energy transition” is often linked with aims of placing power production units close to consumption to regional balance divergence between power production and consumption patterns. Supporters expect a minor transmission grid expansion requirement from such a “decentralized energy transition”.Against this background the article addresses the practice of grid planning in Germany as a focal point of the spatial energy policy. In this regard the role of transmission capacity planning is crucial. It is directly based on aims and measures of energy policy and thereby connects energy policy with transmission grid planning. The Federal Network Agency meanwhile has established sensitivity analysis as an instrument to check policy options with regard to their impacts on grid extension requirements. This instrument however could also be used to consider alternative paths in order to develop a systematic weighting regulation approach with integrated public participation based on well-grounded impact analysis.
Keywords: Capacity planning; Transmission grid expansion; Energy transition; Regionalisation; Centrality